2013
DOI: 10.3109/02713683.2013.822896
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mild Ocular Surface Stimulation and Concentration on Spontaneous Blink Parameters

Abstract: Purpose This exploratory, pilot study compared the effects of concentrating on a visual task and a very mild ocular surface air stimulus on multiple blink parameters. Methods Ten subjects participated in this study. There were 2 visits, one with an ocular surface air stimulus (AS) and one without (NS). The AS was set at a level barely perceptible by subjects (approximately 0.6m/sec at the eye). At each visit, subjects performed a high (HC) and low concentration (LC) task. Blinking was tracked and tear-film b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Many studies have shown increased spontaneous blinking when the ocular surface is stimulated [315317]. Recently, Wu et al showed a linear increase in blink rate with increasing air flows applied on the ocular surface [318].…”
Section: Neural Regulation Of Eye Blinksmentioning
confidence: 99%
“…Many studies have shown increased spontaneous blinking when the ocular surface is stimulated [315317]. Recently, Wu et al showed a linear increase in blink rate with increasing air flows applied on the ocular surface [318].…”
Section: Neural Regulation Of Eye Blinksmentioning
confidence: 99%
“…Many blinks are partial (Cruz et al, 2011; Doane, 1980; Harrison et al, 2008; Himebaugh et al, 2009; Wu et al, 2014) and this makes the effects of the turning point more visible than the full blinks in the optical systems we have used. Fig.…”
Section: Turning Pointmentioning
confidence: 99%
“…This is just at the sensory threshold (Liu et al, 2009). For a thinning rate of 10 μm/min, this value is increased to about 900 mOsM, while at 20 μm/min, it is increased to very large values, 1830 mOsM at 25 s. It is likely that a subject would blink before reaching such large values, but these values may possibly be reached if the subject is performing a task with intense concentration or is in a controlled experiment and asked not to blink (Cruz et al, 2011; Wu et al, 2014). Results at other times are given in Table 1; such long times are not needed to reach what is currently thought to be high osmolarities in the menisci over the cornea.…”
Section: Interblinkmentioning
confidence: 99%
See 2 more Smart Citations